2020
DOI: 10.3892/etm.2020.9436
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine inhibits the PSD95‑NMDA receptor interaction to promote functional recovery following traumatic brain injury

Abstract: The present study examined the effects of dexmedetomidine (Dex) on cognitive and motor recovery in mice following traumatic brain injury (TBI). TBI induces synaptic damage, which leads to motor dysfunction and cognitive decline. Although Dex is known to induce neuroprotection, its role following TBI remains unknown. In the present study, male C57BL/6 mice (8 weeks old; n=72) were subjected to cortical impact injury to generate a TBI mice model. Mice were divided into four groups: TBI, sham, TBI + vehicle, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In Zhao’s study, they found that post-synaptic density 95 (PSD95) formed a complex with the N-methyl-D-aspartic acid (NMDA) receptor subunit (NR2B) and neuronal nitric oxide synthase (nNOS), inducing neuronal death post-TBI. After administering dexmedetomidine, the PSD95–NR2B–nNOS interaction was decreased efficiently, and they found dexmedetomidine could enhance cognitive and motor recovery following TBI [ 9 ]. Another study showed that dexmedetomidine can alleviate cerebral ischemic reperfusion injury in rats by increasing the α2-adrenergic receptor and blocking JNK phosphorylation and the activation of caspase-3 [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zhao’s study, they found that post-synaptic density 95 (PSD95) formed a complex with the N-methyl-D-aspartic acid (NMDA) receptor subunit (NR2B) and neuronal nitric oxide synthase (nNOS), inducing neuronal death post-TBI. After administering dexmedetomidine, the PSD95–NR2B–nNOS interaction was decreased efficiently, and they found dexmedetomidine could enhance cognitive and motor recovery following TBI [ 9 ]. Another study showed that dexmedetomidine can alleviate cerebral ischemic reperfusion injury in rats by increasing the α2-adrenergic receptor and blocking JNK phosphorylation and the activation of caspase-3 [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a highly selective central agonist of the α2 adrenergic receptor, dexmedetomidine has been administered in many therapeutic procedures safely and efficiently [ 6 , 7 , 8 ]. Animal studies showed that dexmedetomidine reduced neuronal death by protecting against neural autophagy and neuroinflammation, enhanced cognitive and motor recovery following traumatic brain injury, and alleviated cerebral ischemic reperfusion injury [ 9 , 10 , 11 ]. Hence, dexmedetomidine was recommended in patients after craniotomy in recent years [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Lia et al suggested that DEX could reduce the apoptosis of nerve cells in patients with brain injury caused by oxidative stress through the proliferator-activated receptorgamma coactivator 1α (PGC-1α) pathway, and DEX decreased MDA levels while increasing SOD and GPX levels (Xu et al, 2014;Huang and Jiang, 2019). Zhao et al (2021) showed that the expression of postsynaptic density protein 95 (PSD95) was decreased in TBI mouse brain tissues, while the levels of the PSD95-N-methyl-D-aspartic acid (PSD95-NMDA) complex were significantly increased. Excessive levels of the PSD95-NMDA complex can lead to the massive release of NO and activate matrix metallopeptidase 9 (MMP9), thus inducing apoptosis, and DEX can inhibit the formation of the PSD95-NMDA complex.…”
Section: Dex Can Reduce Apoptosis Induced By Oxidative Stressmentioning
confidence: 99%
“…However, the CT scan cannot detect the skull base, posterior fossa, and non-hemorrhagic injuries [ 7 ]. Due to its inability to examine shear injuries of white matter, corpus callosum, and brainstem, the CT scan has little help in the examination of the patients with severe illness and does not show substantial advantages in the long-term prognosis [ 8 ]. With the continuous development and progress of imaging technology, magnetic resonance imaging (MRI) has been rapidly developed, which provides the reference and basis for the diagnosis of craniocerebral injury.…”
Section: Introductionmentioning
confidence: 99%